Pots & plays - Taplin, Oliver (J. Paul Getty Museum, 2007)
Setting the scenes – The pots – Aeschylus – Sophocles – Euripides – Fragments of Euripides – Unknown tragedies – Index of vases
Includes bibliographical references and index
Keywords: Vase-painting; Greek; Theater in art; Greek drama (Tragedy)